A Highly Accurate Numerical Method for Flow Problems with Interactions of Discontinuities (Journal of Computational Mathematics, 2002)
A type of shock fitting method is used to solve some two and three dimensional flow problems with interactions of various discontinuities. The numerical results show that high accuracy is achieved for the flow field, especially at the discontinuities. Comparisons with the Lax-Friedrichs scheme and the ENO scheme confirm the accuracy of the method.